Public sector marketing and brand image of the Congress of the Republic of Peru - Benites Salas, Yolanda Liliana (2025)
The objective of this research is to determine how public sector marketing relates to the brand image of the Congress of the Republic among citizens in the district of La Victoria in 2022. An observational, correlational, cross-sectional study was used, with a sample of 384 citizens in the district of La Victoria, selected through non-probabilistic convenience sampling. Two Likert scale questionnaires were used to measure the study variables. The Spearman's Rho correlation test was used with a significance level of 0.05. The results showed a positive, moderate and significant correlation between public sector marketing and brand image (Rho = 0.578, p < 0.05). The relationship was stronger in the product and price dimensions, with values of Rho = 0.543 and Rho = 0.536, respectively. The promotion dimension obtained a Rho = 0.442 and the place dimension, a Rho = 0.309. In conclusion, public sector marketing, as well as each of its dimensions (product, price, place and promotion), is significantly related to the brand image of the Congress of the Republic among citizens in the district of La Victoria.